Utilisation of Natural Resources for Ecotourism Development in Community Service Programme - Mila Sari; Fathia Rahmadini; Kalasta Ayunda Putri; Handri Maika Saputra; Rafika Aini (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
Community-based ecotourism (CBET) is one of the most popular ecotourism programs in the world. This study uses a qualitative descriptive approach that aims to comprehensively describe the process of utilizing natural resources in developing ecotourism through community service programs. Data collection was conducted through several main techniques, namely participant observation, in-depth interviews, and focus group discussions (FGDs). Focus group discussions were aimed at key informants who had knowledge and active involvement in ecotourism development, to explore experiences, challenges, and strategies used in program implementation. Thematic analysis techniques were used to identify patterns, main themes, and relationships between variables in the context of ecotourism based on the use of natural resources. The results of the quantitative descriptive analysis show that the level of community participation in the ecotourism activities is in the very high category, with an average score of 4.21 out of 5 and a participation frequency of 87.5%. High community involvement, the formation of institutions such as Pokdarwis, and increased environmental understanding indicate that the Community-Based Ecotourism model can be implemented effectively at the village level.